Highlights of practical applications of agents, multi-agent systems, and sustainability : the PAAMS collection : International Workshops of PAAMS 2015, Salamanca, Spain, June 3-4, 2015. Proceedings /: the PAAMS collection : International Workshops of PAAMS 2015, Salamanca, Spain, June 3-4, 2015. Proceedings. (2015) - Unknown
No abstract available